THE IMPLEMENTATION OF CRITICAL DISCOURSE ANALYSIS IN AN ENGLISH CLASSROOM - Moh. Fuadul Matin (Indonesian EFL Journal, 2017)
: This research reports on the implementation of a teaching program on an English classroom which incorporated the principles of Critical Discourse Analysis (CDA). This study can be regarded as part of Critical Language Awareness (CLA), a pedagogical wing of CDA, since it implemented CDA into a classroom practice. In this respect, this study examines the implementation of the principles of CDA in an English classroom, the effects it brings towards students’ critical reading, and students’ responses towards the teaching program. The study employed a qualitative case study which involved eighth grade of Junior High School students at SMP Al-Maliki Bojonegoro in odd semester 2016-2017. It used several data collection techniques including a phase of teaching in which the researcher acted as the participant observer, as well as students’ reflective journals, and questionnaire. Data from all sources revealed that the implementation of CDA’s principles develops students’ critical reading in general. It also demonstrated students’ positive responses towards the teaching program that it gave plenty of new insights for them and improved their critical reading as well. All these results indicate that the infusion of CDA into the teaching of reading is considerably effective in enhancing students’ critical reading.Keywords: critical discourse analysis, critical language awareness, students’ critical reading